Analysis of Raw Material Inventory on the Sale of Hand Woven Gloves at UD. Ulos Tarutung Twins - Devisa Romasi Hutasoit; Rosalinda Septiani Sitompul (Jurnal Mantik, 2021)
In a company engaged in manufacturing, the process of procuring inventory is a very important process, without the existence of inventory, the company will face the risk of difficulty in the continuity of the production process.The research method used is descriptive qualitative. The data collection techniques used were interviews and observation. The data analysis techniques used in this research are: (1) Collecting information about the amount of raw material inventory in 2019. (2) Processing these data to determine the control of raw material supplies based on company policy. (3) Analyzing the processed data using the Economic Order Quantity (EOQ) method. This research was based on the weaving supply system of UD. Ulos Tarutung's twins are not good enough so that the available supply is not optimal. The purpose of this research is to find out how the supply of raw materials using the EOQ method in determining the optimal number of orders, knowing the level of reorder (Re Order Point), as well as the amount of safety stock (Safety Stock). The conclusion of the results of this study is the results of the application of the EOQ method to the supply of cotton yarn as raw material proved to be more efficient. This can be seen from the cost efficiency before EOQ Rp. 2,813,968 and after the application of EOQ 1,403,909, the cost efficiency after applying the method was Rp. 1,410,059. To anticipate the fluctuation of demand for safety stock (Savety Stock), which is provided of 8 packs, and for re-order level (Re Order Point) 19 packs. The method used to calculate this forecast is the moment trend method. The purpose of this research is to design and build an application for sales forecasting using the Trend Moment method for decision making in knowing the number of sales of UD tenu sarongs. Ulos Tarutung twins. With the forecasting system for the sale of woven sarong goods using the trend moment method, it can assist the company in making decisions about the procurement of stock quantities and predicting the number of sales of goods in a certain period so as to minimize excess or shortage of goods stock at UD. Ulos Tarutung twins.